2022
DOI: 10.3390/adolescents2020019
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Analysis of Cyberbullying Victimization and Its Associations with Suicidality: Findings from the 2019 Youth Risk Behavior Survey

Abstract: Cyberbullying victimization (CV), a widespread experience in adolescence, is associated with increased depression and suicidality. However, few studies have taken a gender approach when investigating the association between CV and suicidality, despite research that indicates disparate experiences by gender for both CV and mental health. We conducted a secondary data analysis of the 2019 Youth Risk Behavior Survey (N = 10,309; 50.1% girls), a cross-sectional survey drawn from a representative sample of US high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…When the relationship between gender and cyberbullying was evaluated, it has been shown in the studies that while being cyberbullied was more common in girls, cyberbullying was more common in boys (22,26,27). Following the literature, cyber victimization was higher among girls in our study.…”
Section: Discussionsupporting
confidence: 70%
“…When the relationship between gender and cyberbullying was evaluated, it has been shown in the studies that while being cyberbullied was more common in girls, cyberbullying was more common in boys (22,26,27). Following the literature, cyber victimization was higher among girls in our study.…”
Section: Discussionsupporting
confidence: 70%
“…35 Cyberbullying victimisation studies have shown a high risk of suicide among adolescents, with depression being the main clinical cause. 36 The rise in cyberbullying not only places a threat to the state of public health but also threatens access to higher education and learning. 37 The Inclusion Index proposed by Booth and Ainscom necessitates the need to institutionalise policy reforms that cater to sexual and gender minorities and students with special needs.…”
Section: Cyberbullying During the Covid-19 Pandemicmentioning
confidence: 99%